The professor and the Juita NGO smart partnership in social welfare work - Jamilah Ariffin (MPH Group Publishing, 2013)
This book provides readers with an opportunity to understand the life experience of a professor who had to leave the ivory tower in Kuala Lumpur in 1995 and be transferred to Johor to take over the leadership of a Non-Governmental Organization for wives of state elected representatives called Juita.